SERUM OESTRADIOL -17Ã¢ AND PROGESTERONE PROFILE IN HAMPSHIRE GILTS FOLLOWING SYNCHRONIZATION OF OESTRUS BY PGF 2âˆ ANALOGUES - S. SINHA3, H. KONCH1; ARUP DUTTA K. K. BARUAH (Indian Journal of Animal Production and Management, 2017)
Following synchronization of oestrus by PGF2-âˆ analogue, serum oestradiol-17Ã¢ andprogesterone concentration during different stages of gestation were carried out in a total 18pubertal Hampshire gilts reared in the Base Pig Breeding Farm, Department of AnimalHusbandry and Veterinary, Government of Assam, Khanapara,Guwahati. The pubertal giltswere divided in to three groups viz. Group I and II as treated and Group III as control. Giltsof Group I received 5ml Iliren during luteal phase of cycle whereas gilts of Group II received Serum oestradiol -17Ã¢ and progesterone profile in Hampshire giltstwo injection of 5ml Iliren at 11 days apart. The mean serum oestradiol-17Ã¢ andprogesterone showed significantly (P